Mazo un vidējo uzņēmumu attīstība un atbalsts Latvijā - Brīdaka, Jana (Latvijas Universitāte, 2010)
Bakalaura darba tēma ir „Mazo un vidējo uzņēmumu attīstība un atbalsts Latvijā”. Darba procesā parādīts, ka mazo un vidējo uzņēmumu politikas un atbalsta programmu pilnveidošana sekmē mazo un vidējo uzņēmumu attīstību, un līdz ar to arī valsts stabilizāciju. Bakalaura darbā ir apskatītas Uzņēmējdarbības būtība un nozīme, mazo un vidējo uzņēmumu raksturojums, nacionālās MVU atbalsta programmas Latvijā. Bakalaura darba noslēgumā tiek aprakstīti galvenie uzņēmuma uzsākšanas priekšrocības un trūkumi. Bakalaura darbs varētu būt izmantojams mazo un vidējo uzņēmumu problēmu risināšanā, kā arī veidojot nākotnes attīstības politiku. Atslēgvārdi: Mazie un vidējie uzņēmumi, uzņēmējdarbības politika, MVU atbalsta programmas.

The theme of bachelor thesis is „Small and Medium Enterprises Development and Support in Latvia”. During work process it is shown, that improvement of policy and support programs promotes the development of small and medium enterprises as well as stabilization of state. In the bachelor thesis is discussed the substance and significance of entrepreneurship, the characterization of small and medium enterprises and description of National SME support program in Latvia. Most important advantages and disadvantages of business inception are described in the conclusion. The bachelor thesis could be used in issue solving for small and medium enterprises as well as modeling future development policy. Keywords: small and medium enterprises, business policy, SME support programs.
Development and support of small and middle enterprises in Latvia
Keywords: Ekonomika